Precisión diagnóstica y riesgo de implante secundario en el estudio de carcinoma endometrial por histeroscopía - Miranda M., Ignacio; Herane C. , Eduardo; Cárdenas, Juan Pablo; San Martín, Marcelo; Franulic, Lenka; Selman A., Alberto (Revista Hospital Clínico Universidad de Chile, 2007)
Adenocarcinoma of the endometrium is the most common malignancy of the female genital tract in developed countries. Hysteroscopy has turned into a widely used procedure to improve curettage-biopsy sensibility. Uncertainties have arisen about the hysteroscopic endometrial carcinoma diagnostic sensibility its safety due to the possibility of peritoneal seeding. A MED-LINE and Cochrane Library search was performed. We found that the hysteroscopic diagnosis has low incidence of complications and high diagnostic rate for endometrial carcinoma. There are cytological, case reports and retrospectives studies showing both an increase and also non-increase of seeding risk of cancer cells.